Biased Retention of Environment-Responsive Genes Following Genome Fractionation - Beringer, Marc; Choudhury, Rimjhim Roy; Mandáková, Terezie; Grünig, Sandra; Poretti, Manuel; Leitch, Ilia J; Lysak, Martin A; Parisod, Christian (Molecular biology and evolution, 2024)
The molecular underpinnings and consequences of cycles of whole-genome duplication (WGD) and subsequent gene loss through subgenome fractionation remain largely elusive. Endogenous drivers, such as transposable elements (TEs), have been postulated to shape genome-wide dominance and biased fractionation, leading to a conserved least-fractionated (LF) subgenome and a degenerated most-fractionated (MF) subgenome. In contrast, the role of exogenous factors, such as those induced by environmental stresses, has been overlooked. In this study, a chromosome-scale assembly of the alpine buckler mustard (Biscutella laevigata; Brassicaceae) that underwent a WGD event about 11 million years ago is coupled with transcriptional responses to heat, cold, drought, and herbivory to assess how gene expression is associated with differential gene retention across the MF and LF subgenomes. Counteracting the impact of TEs in reducing the expression and retention of nearby genes across the MF subgenome, dosage balance is highlighted as a main endogenous promoter of the retention of duplicated gene products under purifying selection. Consistent with the "turn a hobby into a job" model, about one-third of environment-responsive duplicates exhibit novel expression patterns, with one copy typically remaining conditionally expressed, whereas the other copy has evolved constitutive expression, highlighting exogenous factors as a major driver of gene retention. Showing uneven patterns of fractionation, with regions remaining unbiased, but with others showing high bias and significant enrichment in environment-responsive genes, this mesopolyploid genome presents evolutionary signatures consistent with an interplay of endogenous and exogenous factors having driven gene content following WGD-fractionation cycles.
Keywords: molekulární evoluce; Genome, Plant; dosage balance; Gene Expression Regulation, Plant; duplikace genu; Brassicaceae; Stress, Physiological; genom rostlinný; subgenome dominance; Evolution, Molecular; transpozibilní elementy DNA; fyziologický stres; conditionally expressed genes; Gene Duplication; transposable elements; environmental stress; regulace genové exprese u rostlin; whole-genome duplication; DNA Transposable Elements